Anatomia ecológica foliar de espécies da caatinga - Barros, Ileane Oliveira (2010)
In semiarid environments water availability is a main limiting factor for plants. A combination of characteristics can contribute to saving water, including the anatomical ones. The anatomical attributes often associated with environments of water restriction are called xeromorphic. The leaves are organs commonly exposed to sunlight which have large areas of transpiration. It is assumed that the leaves of species in the caatinga exhibit some morphological and anatomical attributes that enable them to withstand the conditions of semiarid environment in which they live. Thus, we performed anatomical collection and processing according to standard techniques in thirteen leaves of species common in the caatinga. Xeromorphic characteristics observed are possibly related to water economy. Three functional groups were distinguished with respect to such attributes. The first (G1), consists of deciduous species with dense indument. The second (G2), consists mainly deciduous, and a distinctive feature is mucilage in the epidermal cells. In the third (G3) are two deciduous and three evergreen with tougher leaves and thick cuticle. These groups have phylogenetic influence, though some close relationships can not be attributed just to kinship, indicating other similarities, probably functional, with respect to the use of the main limiting factor in semiarid environments: water. The various ways of exploiting the same resource suggest niche differentiation, resulting in the different groups, while sharing characteristics may reflect the limited number of adaptive solutions that direct possible convergences responsible for characteristics shared within a group phylogenetically distant.